2018
DOI: 10.1097/wco.0000000000000602
|View full text |Cite
|
Sign up to set email alerts
|

Advances in management of Guillain–Barré syndrome

Abstract: New diagnostic tools may help to have early and accurate diagnosis in difficult GBS cases. Increased knowledge on the pathophysiology of GBS forms the basis for development of new, targeted, and personalized treatments that hopefully improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
1
19
0
2
Order By: Relevance
“…Patients may benefit from steroids, although intravenous immunoglobulin or plasma exchange is often required. 5 Although this patient did present with ataxia and loss of lower reflexes, he did not have progressive distal to proximal spread of symptoms typical for GBS.…”
Section: Questions/discussion Points Partmentioning
confidence: 70%
“…Patients may benefit from steroids, although intravenous immunoglobulin or plasma exchange is often required. 5 Although this patient did present with ataxia and loss of lower reflexes, he did not have progressive distal to proximal spread of symptoms typical for GBS.…”
Section: Questions/discussion Points Partmentioning
confidence: 70%
“…The use of imaging studies such as peripheral nerve ultrasound and MRI are helpful diagnostic tools to diagnose inflammatory peripheral nerve roots [34].…”
Section: Diagnosis Of Guillain-barre Syndrome and Miller Fisher Variantmentioning
confidence: 99%
“…should be considered. Since CSF may include normal levels of cells and proteins, especially at the onset of presentation, its utility is questionable and is most appropriate in cases of diagnostic doubt [6,11,[18][19][20]. Electroneuromyography (ENMG): Demonstrates evidence of demyelination, allowing to confirm or clarify the injured anatomical site.…”
Section: Complementary Examsmentioning
confidence: 99%
“…Plasma exchange is performed at 200-250mL/kg, four to six sessions over eight to ten days, while intravenous immunoglobulin is administered at a dose of 400mg /kg/day for five days [12,17]. Corticosteroid therapy is not recommended because it is not sufficient, although some studies have shown short-term therapeutic benefits when associated with intravenous human immunoglobulin [17,[19][20][21]. Pharmacological treatment of pain, which is a complaint in about two-thirds of cases, cannot be forgotten.…”
Section: Predictors Of Acute Respiratory Failure [17]mentioning
confidence: 99%